Mental Toughness Analysis in Handball Athletes Based on Gender and Length of Practice - Nadila Agustina Iskandar; Yusuf Hidayat; Mudjihartono (Journal of Physical Education Health and Sport, 2025)
This study aims to find out the difference in the mental toughness of  handball athletes based on gender and length of practice, as well as to find out the interaction between the three variables. This research method uses a descriptive quantitative approach. The data in this study was obtained from 56 athletes, 28 handball athletes from Bogor Regency and 28 handball athletes from the city of Bandung, each contingent consisting of 14 male athletes and 14 female athletes. The data collection technique used the Sport Mental Toughness Quistionnaire (SMTQ) compiled by Sheard. Data analysis in this study used independent sample t-test and one way anova. The results showed that there was a significant difference by sex with (Sig. 2-tailed = 0.000; p<0.05) especially on the confidence subscale, and the length of practice had an effect (Sig. = 0.006; p<0.05) on mental toughness, athletes who trained >2 years showed a higher level of mental toughness than the <1 year group. In conclusion, while gender differences primarily affect confidence, a training duration of more than two years is the key factor in achieving stable mental toughness among PORPROV handball athletes.